(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This study was conducted with the aim of finding out the difference in the level of student aggression behavior reviewed from gender and type of school in Labuhan Batu Regency in 2019, this study is quantitative research with a sample of 346 students, sampling using Random Sampling. The instrument used is the aggression behavior scale. Data analysis with the Mann-Whitney Test. The results of the study showed that there was a difference in aggression behavior between men and women, where male aggression behavior was higher than female aggression behavior